1982
DOI: 10.1007/bf02914032
|View full text |Cite
|
Sign up to set email alerts
|

The ultrastructure of germinating barley seeds. I. Changes in the scutellum and the aleurone layer in Nordal barley

Abstract: The ultr~tstructure of the scutellum and the aleurone layer has been examined in seeds of Nordal barley following malting for 0, 30, 72, 120 and 162 hours at 15 ~ Thick sections from the seeds were stained with Calcofluor White M2R New and examined in the light microscope to determine the extent of cell wall degradation in the endosperm.The changes in the scutellar parenchyma cells include degradation of the protein bodies and the appearance of vacuoles and prominent amyloplasts. The analysis of a serially sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
19
0

Year Published

1983
1983
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 44 publications
2
19
0
Order By: Relevance
“…The abundant stacks and arrays of RER of the active aleurone cells observed at the EM level had an appearance and location similar to those of the fluorescence produced by DiOC6(3) staining, which leads us to believe that this fluorescence represents mainly ER in these cells. These structural and ultrastructural changes observed in the aleurone cells of Funks G4646 and Illinois 677a are similar to what has been described in germinating barley grains (11), and these changes have been functionally correlated with the synthesis and secretion of hydrolases, including a-amylase (14). The proliferation of RER and numerous dictyosomes in particular suggests that the endomembrane system plays a key role in a-amylase synthesis and secretion (8,15).…”
Section: Discussionsupporting
confidence: 72%
“…The abundant stacks and arrays of RER of the active aleurone cells observed at the EM level had an appearance and location similar to those of the fluorescence produced by DiOC6(3) staining, which leads us to believe that this fluorescence represents mainly ER in these cells. These structural and ultrastructural changes observed in the aleurone cells of Funks G4646 and Illinois 677a are similar to what has been described in germinating barley grains (11), and these changes have been functionally correlated with the synthesis and secretion of hydrolases, including a-amylase (14). The proliferation of RER and numerous dictyosomes in particular suggests that the endomembrane system plays a key role in a-amylase synthesis and secretion (8,15).…”
Section: Discussionsupporting
confidence: 72%
“…In malting barley and other germinating cereal grains, it has been established that features indicating cellular activity, and production of hydrolases and amylases, are initiated in the scutellum followed by the aleurone layer, and that degradation of endosperm cells starts in the vicinity of the scutellum. [9][10][11] Intact oil bodies thought essential for optimal germination conditions are challenged by their fused state in storage tissues of the oat endosperm. The implications of their fusion for germination and end use quality remain to be determined.…”
mentioning
confidence: 99%
“…In rice, however, newly formed plastids in endosperm contained multiple starch granules. On the other hand, Gram (1982) reported that lipid bodies decrease in number and become smaller in size during germination, while mitochondria develop well, which are thought to be the characteristics of the high metabolic activity. Figure 15 shows a high magnification of a newly formed plastid adjacent to the cell wall.…”
Section: Scanning Electron Microscopic Observationmentioning
confidence: 99%